A brief account of Julius Planer's life and research - Bilyy, R.; Lutsyk, A. (Condensed Matter Physics, 2010)
A brief account of the life and research activities of Julius Planer is presented. Professor Planer is a scientist who lived one and half century ago. However, his studies, in particular, during the years when he headed Department of Anatomy at Universit ¨ at in Lemberg, nowadays known as the Ivan Franko National University of Lviv in Ukraine, were essential to a modern understanding of liquid crystals. While working at Lviv University, Planer also made several landmark contributions to biomedical science. Представлено стислий огляд життєвого шляху та наукової діяльності Юліуса Планера. Професор Планер жив півтора сторіччя тому, проте його наукові дослідження, зокрема, протягом часу коли він очолював кафедру анатомії Львівського університету (зараз Львівський національний університет імені Івана Франка) стали визначальними на шляху сучасного розуміння рідких кристалів. Працюючи у Львівському університеті, Планер також зробив кілька значних відкриттів у біомедичній галузі.